Ruminal passage rate and digestibility of fiber from dairy cows consuming diets containing alfalfa and orchardgrass hays with different concentrations of undegradable neutral detergent fiber - H. Galyon; B.A. Corl; G. Ferreira (Journal of Dairy Science)
ABSTRACT: This study aimed to evaluate the effect of feeding diets with different fractions of undegraded NDF (uNDF) and potentially degradable (pdNDF) on ruminal NDF degradation and passage kinetics of lactating dairy cows. Six rumen-cannulated (533 ± 43 kg BW and 122 ± 15 DIM) and 6 noncannulated (558 ± 62 kg BW and 126 ± 16 DIM) primiparous Holstein dairy cows were randomly assigned to 1 of 2 experimental diets in a crossover design with two 28-d periods. The experimental diets were formulated to include either alfalfa hay (ALFA) or orchardgrass hay (ORCH) in addition to corn silage. Rations were formulated to contain 30% NDF (DM basis), where the concentrate, corn silage, and each of the hays provided one third of the dietary NDF. The marker dilution technique was used to measure the passage rate using a pulse dose of marked corn silage fiber. On d 17 and 24 of each period, ruminal contents were evacuated to determine ruminal pool size. Following the return of the ruminal contents containing the pulse dose of marked corn silage to the rumen, ruminal grab samples were collected at 0, 3, 6, 9, 12, 24, 36, 48, 60, and 72 h. Samples from each time point were separated into solids and liquid, and the solids were analyzed for NDF, uNDF, and marker concentration. Alfalfa hay had a higher concentration of CP (16.4% vs. 10.7%) and a lower concentration of NDF (38.0% vs. 63.2%) than orchardgrass hay. Alfalfa hay had a greater concentration of uNDF than orchardgrass hay (36.5% vs. 32.8% uNDF; NDF basis). Cows consuming the ALFA diet had similar milk yield (39.1 kg/d) and similar milk fat and protein concentrations (3.72% fat and 3.24% protein, respectively) than cows consuming the ORCH diet. Cows consuming the ALFA diet consumed more DM (26.7 vs. 24.6 kg/d) and uNDF (2.7 vs. 2.3 kg/d), than cows consuming the ORCH diet. Cows consuming the ALFA diet digested more NDF and pdNDF than cows consuming the ORCH diet (3.3 vs. 2.8 kg/d). Even though cows consuming the ALFA diet had a smaller pool size of NDF than cows consuming the ORCH diet (5.4 vs. 6.7 kg), the pool size of uNDF did not differ between groups (2.4 kg). Cows consuming the ALFA diet had a faster rate of passage of uNDF than cows consuming the ORCH diet (5.02%/h vs. 4.03%/h). This translated into a shorter mean retention time of uNDF for cows consuming the ALFA diet relative to cows consuming the ORCH diet (21.0 vs. 26.2 h). Overall, cows consuming diets containing alfalfa hay had a faster ruminal passage rate and a shorter mean retention time of uNDF than cows consuming diets containing orchardgrass hay, and this occurred despite the greater concentrations of dietary uNDF in the alfalfa-based diet. These findings suggest that the kinetics of ruminal digestion and passage influence NDF degradation in ways beyond uNDF concentration or forage quality.